Relationship Of Food Consumption With Disease Hypertension In Elderly at Panti Jompo Yayasan Guna Budi Bakti Medan Labuhan - Kurniawan, Ihsan Isan (Journal of Nursing Update, 2019)
Based on WHO data (World Health Organition), around 972 million people in the world or 26.4% of people worldwide have hypertension, the figure is likely to increase to 29.2% in 2025. Of the 972 million hypertension, 333 million are in developed countries and the remaining 639 are in developing countries including Indonesia. This research aims to determine the relationship of food consumption with hypertension in the elderly at the Nursing Home in Medan Labuhan Foundation for the Budi Bakti in 2018. The research design is an analytical survey to determine the relationship between two variables with a cross sectional approach. The population in this study were patients who suffered from hypertension in the Nursing Home Foundation Medan Labuhan For Bakti Budi Bakti in 2018 totaling 64 people and a sample of 64 people and using total sampling. The test in this study is Chi-square test. The results of this study showed that 61 (95.3%) of the majority had poor food consumption, and the majority of hypertensive diseases were as heavy as 45 respondents (70.3%), bivariate statistic test results showed that there was a relationship between food consumption and hypertension with p value -Velue = 0.004.     The conclusion in this study is that there is a relationship between food consumption and hypertension is p-velue = 0.004 α 0.05, so Ha is accepted. Suggestions for further researchers to be able to examine the causes and relationship of food consumption with hypertension.